PENINGKATAN MINAT DAN KREATIVITAS SISWA MELALUI PORTOFOLIO DIGITAL MENGGUNAKAN GOOGLE SITES DALAM PEMBELAJARAN IPS - Kiswarini, Dian; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine whether the use of digital portfolios through Google Sites can enhance students’ learning interest and creativity in Social Studies learning. The learning interest and creativity of eighth-grade students in class VIII-F improved after the implementation of Google Sites–based digital portfolios over two instructional cycles. The results indicate that: (1) in the pre-cycle, students’ learning interest in Social Studies was in the low category, reaching 38,75% across all indicators, while creativity was recorded at 37%, showing that students generally demonstrated low interest and low creativity in learning; (2) in Cycle I, students’ learning interest increased to a moderate level with an average score of 60% across all indicators, accompanied by an improvement in creativity to 51%, also categorized as moderate; and (3) in Cycle II, students’ learning interest reached a good category with an average score of 80%, while creativity increased significantly to 82%, classified as very good. Based on the data analysis, it can be concluded that the use of Google Sites–based digital portfolios in Social Studies learning effectively enhances the learning interest and creativity of students in class VIII-F at SMP Negeri 12 Madiun.